Adaptations in triceps surae muscle-tendon unit mechanical properties in elite jumpers - Epro, G.; König, M.; Schade, F.; Karamanidis, K. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to analyse the triceps surae (TS) muscle-tendon unit (MTU) mechanical properties (muscle strength, maximal tendon strain and tendon stiffness) in elite track and field jumpers (long jump, triple jump, high jump, pole vault) over several years, in order to examine potential alterations in the uniformity of adaptation within the TS MTU. The findings demonstrated a higher TS muscle strength and tendon stiffness for the take-off leg in comparison to the swing leg, irrespective of the jumping discipline. Similar symmetry indexes for muscle strength and tendon stiffness indicated to a uniform TS MTU adaptation in healthy elite track and field jumpers. Longitudinal investigation demonstrated greater fluctuations in TS MTU properties over one year in elite jumpers compared to age-matched controls, predominantly for the take-off leg, irrespective of the training period (preparation vs. competition period). Nevertheless, athletes with lower adaptive similarities between muscle and tendon adaptation may experience temporary increased demand on the tendon and potentially be at greater risk for tendon injuries.